Synthesis of All Stereoisomers of RK460 and Evaluation of Their Activity and Selectivity as Abscisic Acid Receptor Antagonists. Issue 14 (12th February 2019) - Mikame, Yu; Yoshida, Kazuko; Hashizume, Daisuke; Hirai, Go; Nagasawa, Kazuo; Osada, Hiroyuki; Sodeoka, Mikiko
Abstract: The PYR/PYL/RCAR protein families have recently emerged as receptors of the phytohormone abscisic acid (ABA, 1 ), which regulates plant responses to environmental stress. These families have multiple members with different physiological actions, and so selective agonists or antagonists are needed both as tools to elucidate functional differences and as lead compounds for agrochemicals. We previously identified RK460 ( rac ‐3 a ) as a PYR1‐selective antagonist, and showed that it possesses five stereocenters on a 6, 5‐ cis ‐bicyclo skeleton. Here, we synthesized all the stereoisomers of RK460 and evaluated their activity towards a panel of receptors. Relative stereochemistry as well as absolute stereochemistry was important for selective action. Abstract : Figuring eight : In order to examine the relationship between stereochemistry and abscisic acid (ABA) receptor antagonist activity, all eight possible isomers of the PYR1‐selective antagonist, RK460, were synthesized. The core structure for the activity was identified, and it was found that inverting the C6 stereochemistry altered the receptor selectivity. Methodology for asymmetric synthesis of RK460 derivatives was also established.